2002
DOI: 10.2343/geochemj.36.113
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Ce anomaly in the REE patterns of peat moss and peat grass in the Ozegahara peatland.

Abstract: The rare earth elements (REEs) of the two major vegetation of the Ozegahara peatland, peat moss (Sphagnum sp.) and peat grass (Carex sp.), were determined. The overall variation of the chondrite-normalized REE patterns was almost identical to that of soil-grown plants except for cerium. Peat moss and peat grass showed no cerium anomaly, while all the soil-grown plants we have surveyed showed negative cerium anomaly. The E H and pH condition to produce the cerium anomaly was discussed and the peatland was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
(17 reference statements)
1
23
0
1
Order By: Relevance
“…Thus, the relative abundance of REEs in terrestrial soil-grown plants, peat vegetation, and algae are distinct from each other. According to our survey, soil-grown plants and algae showed Ce anomalies in their REE patterns, whereas peat vegetation showed no Ce anomaly (Akagi et al, 2002;Fu et al, 1998Fu et al, , 2000Fu et al, , 2001. There is a good theoretical reason for the absence of a Ce anomaly in peat vegetation: the water in peatland soil has too low a pH value and redox potential to oxidize Ce 3+ to Ce 4+ (Akagi et al, 2002).…”
Section: Implications Regarding the Original Plants That Produced Thementioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the relative abundance of REEs in terrestrial soil-grown plants, peat vegetation, and algae are distinct from each other. According to our survey, soil-grown plants and algae showed Ce anomalies in their REE patterns, whereas peat vegetation showed no Ce anomaly (Akagi et al, 2002;Fu et al, 1998Fu et al, , 2000Fu et al, , 2001. There is a good theoretical reason for the absence of a Ce anomaly in peat vegetation: the water in peatland soil has too low a pH value and redox potential to oxidize Ce 3+ to Ce 4+ (Akagi et al, 2002).…”
Section: Implications Regarding the Original Plants That Produced Thementioning
confidence: 99%
“…REEs in plants, with the exception of Ce, behave coherently during incorporation into the plant from the environment (Fu et al, 2001). Thus, the relative abundances of REEs in the environment are more or less preserved in plants (Akagi et al, 2002;Fu et al, 1998Fu et al, , 2000Fu et al, , 2001Wyttenbach et al, 1998).…”
Section: Separation Of Rees Into Acetic Acid Soluble and Acetic Acid mentioning
confidence: 99%
See 2 more Smart Citations
“…Freeman et al (2001) reported the involvement of phenolic compounds promoting the decay of peat, which was activated by the presence of oxygen. The whole of the Ozegahara peatland is a reducing environment, buffered with the Fe 2+ -FeOOH system (Akagi et al, 2002). The inactivation and/or lack of such molecules in reducing conditions might be the reason for good preservation of "lignin" in the Ozegahara peatland.…”
Section: Decay Of Holocellulosementioning
confidence: 99%